Diversification, government support, and firm performance - Lan Nguyen-Thi-Huong; Duy Van Nguyen; Loc Xuan Tran (Cogent Business & Management, 2023)
Many companies have been and are implementing diversification to take advantage of capital, reduce risks, and increase revenue for enterprises. At the same time, government support is considered to have positive implications for companies. This study was conducted to assess the impact of diversification and government support on the firm performance of small and medium enterprises (SMEs) in Vietnam. Data was collected on 1,342 SMEs in Vietnam from 2011 to 2015. The analysis results show that diversification has a positive effect on firm performance (through return on assets). However, diversification has no impact on return on equity. The results show that the resource-based view theory is supported when enterprises implement meaningful diversification. The study also shows that the trade-off theory is supported when companies diversify. Government support has no impact on firm performance. The research will help enterprises orient themselves appropriately when deciding to diversify or register and receive support from the government.
Keywords: 650; business model; Diversification; firm performance; government support; smes; Vietnam